Renewable and Non-renewable Electricity Consumption-Growth Nexus: Evidence From Emerging Market Economies - Apergis, Nicholas; Payne, J. (Elsevier, 2011)
This short communication examines the relationship between renewable and non-renewable electricity consumption and economic growth for 16 emerging market economies within a multivariate panel framework over the period 1990–2007. The Pedroni [16] and [17] heterogeneous panel cointegration tests indicate there is a long-run equilibrium relationship between real GDP, renewable electricity consumption, non-renewable electricity consumption, real gross fixed capital formation, and the labor force. However, the long-run elasticity estimate for renewable electricity consumption is positive, but statistically insignificant. The results from the panel error correction model reveal unidirectional causality from economic growth to renewable electricity consumption in the short-run and bidirectional causality in the long-run. Furthermore, there is bidirectional causality between non-renewable electricity consumption and economic growth in both the short-run and long-run.